Multimodality of media texts – main assumptions of audiovisual texts analysis illustrated by TV weather forecast. A German studies perspective - Mac, Agnieszka (Papers in Linguistics, 2022)
The article outlines the main assumptions of multimodal text linguistics in the context of research into contemporary media texts. Linguistic research requires a holistic view of the form and content of a text, including not only the linguistic level but also other sign systems (images, music, sounds, and all their combinations). Such a view makes it possible to carry out a proper analysis of multimodal texts. In the first part of the article, characteristics of media texts are presented. For this purpose, multimodal text and text design are defined and concepts of construing meaning in multimodal artefacts are briefly discussed. Furthermore, research in this area in German literature of the subject is addressed. Next, elements of multimodal texts are shown as illustrated by television texts, and on this basis, an analysis of television weather forecast is conducted in the second part of the article. In conclusion, it is stressed that analysis of television texts must include all sign systems used in a given broadcasting process taking into account links between them, which is the basis for generating their meaning. Finally, some attention is paid to opportunities and difficulties related to new research approaches.